EMPOWERING YOUNG WOMEN THROUGH BALANCED NUTRITION EDUCATION TO PREVENT ANEMIA: PEMBERDAYAAN REMAJA PUTRI MELALUI EDUKASI GIZI SEIMBANG UNTUK MENCEGAH ANEMIA - Petronela Janggu, Jayanthi; Dafiq, Nur; K Senudin, Putriatri; Hamat, Viviana; Panggor, Atma (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Physical and physiological changes in women aged 10-19 make them prone to anemia. Anemia in adolescents negatively affects cognitive, physical, and emotional development. Objective: The community service aimed to increase youth knowledge regarding balanced nutrition to prevent anemia. This activity was carried out at the Ruteng Tsanawiyah Middle School for young girls in class IX. Method: We conducted some service activities consisting of three stages namely the pre-activity stage, the preparation stage, and the implementation and evaluation stage. The activities included pre-test and post-test, measurement of body weight and height, and nutrition education. The data obtained were analyzed using the Paired T-Test through SPSS 16. Results: It was found that 57% of female adolescents had good nutritional status, 33% were undernourished, and 10% were over nourished. After education, significant results were obtained, with an increase from 54% to 86%. Conclusion: Balanced nutrition education can have a significant impact, namely an increase in knowledge.